Implementing Precision Health Care Program at Hospitals in Indonesia - Satriya Pranata; Shu-Fang Vivienne Wu; Yunie Armiyati; Khoiriyah Khoiriyah; Lin Chun Shing; Ju-Han Liu (Gonabad University of Medical Sciences, 2023)
Background: A precision healthcare approach is needed in the context of the healthcare system, especially as an effort to improve the self-management activities of diabetes patients. Accordingly, this study explores the perception of the possibility of implementing a precision healthcare program in hospitals through interviews with policymakers and health professionals. Methods: The purposive sampling via one-on-one, in-depth semi-structural interviews was conducted to collect the data in this study. The data saturation was achieved after interviewing 17 policymakers and health professionals in the selected hospitals. The participants discussed the possibility of a program being implemented in Indonesia and the challenges to implementing the program, as well as discovering the solutions. The narratives were analyzed by the Colaizzi phenomenological analytic method. Results: The three themes that were identified to illustrate the perception of the possibility of implementing precision health care programs at hospitals in Indonesia were as follows: 1) Precision health care for diabetes related to genetics, big data, and patient preference; 2) Barriers to implementing precision health care in Indonesian hospitals; and 3) The implementation of precision health care succeeded step by step. Conclusion: More time is needed to implement Indonesia's precision healthcare concept. It requires time; however, applying the concept has great potential to be developed in reducing the risk of complications caused by diabetes mellitus in the future.